My words are lovely : studies in the rhetoric of the Psalms - Foster, Robert L. (Robert Louis); Howard, David M., Jr (Library of Hebrew Bible/Old Testament studies, 2008)
This collection of essays advances psalms studies through a concerted focus on the persuasive aim of psalmic poetry, and it offers unique perspectives on rhetorical devices within the psalms. These essays include discussions not only of structure, literary devices, and rhetorical strategies, but the authors also dialogue with classical rhetoric, modern psalms research, and current trends in rhetoric and cognitive science. €Part One discusses various theoretical issues. Several articles discuss lament within the psalms, including the function of appeals to pathos, lament's compensation for.